COMPARATIVE ANALYSIS OF PROFESSIONAL TRAINING TRENDS FOR CIRCULAR ECONOMY SPECIALISTS IN THE REPUBLIC OF FINLAND, THE REPUBLIC OF POLAND, AND UKRAINE - Oleksii Sysoiev (Borys Grinchenko Kyiv Metropolitan University, 2024)
This article presents a comparative analysis of trends in the professional training of circular economy specialists in the Republic of Finland, the Republic of Poland, and Ukraine. The relevance of the issue lies in the global emphasis on environmental preservation and the overall ecology of the planet. In response to these global challenges, the adoption of circular economy models and the professional training of specialists in this field play a significant role. The widespread importance of implementing the circular economy concept in higher education is evident in the active sharing of experiences by various countries in developing educational programs for circular economy specialists. To investigate trends in the professional training of circular economy specialists, Finland, a European leader in circular economy implementation, and Poland, rapidly transitioning to circular economy models, were chosen. A crucial step in summarizing the research results involved conducting a comparative analysis of the organization, content, forms, and methods of professional training for circular economy specialists, identifying common and specific trends in Finland, Poland, and Ukraine. The comparison of trends in professional training for circular economy specialists in Finland, Poland, and Ukraine was conducted based on predefined criteria: motivational, organizational, content-processual, and prognostic-perspective. Proposed further research directions address the crucial issue of professional training for circular economy specialists, vital for the post-war recovery of Ukraine.